The Impact of Digital Technology on Children's Concentration - Alfarisi Salman; M. Ihya Maulana; R. Desyana Putri. Haykal; M. Kurnia Sandi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Digital technology significantly impacts children's concentration. While educational apps and structured media positively influence cognitive development, learning motivation, memory, and problem-solving skills, excessive, uncontrolled use leads to negative effects. These include decreased concentration, language development issues, and dependence on devices, hindering creativity and independence. Rapid, responsive technological interactions accustom children to instant stimuli, making sustained attention difficult. Intense screen exposure can cause impulsivity, distractibility, and reduced focus. Therefore, adaptive and technology-aware parenting is crucial. Parental supervision, balanced integration, and time limits on device usage are essential to maximize benefits and minimize adverse effects on children's concentration and overall development